Characteristics of HIV-infected children born to HIV-positive mothers in Cipto Mangunkusumo Hospital between 2002 and 2007 - Fransisca Mayer; Arwin Akib; Imam Boediman (Indonesian Pediatric Society, 2009)
Background In 2003, the Joint United Nation Program onHIV/AIDS and the World Health Organisation estimatedthat there will be 36.2 million people living with HIV /AIDSthrougout the world by the end of2003, and that 2.1 millionof them will be children less than 15 years old. The profileof children with HIV in the Department of Child Health,Cipto Mangunkusumo Hospital has not been studied.Objective To identify the characteristics of HIV-infectedchildren born to HIV-positive mothers, and to evaluate thePrevention Programme for Mother-to-Child Transmissionat Cipto Mangunkusumo Hospital.Methods This was a cross-sectional study conductedbetween March and May 2008 based on medical records.The study population consisted of all mother-child pairswho were admitted between January 2002 and December2007.Results Between 2002 and 2007,342 children were born toHIV-infected mother, with 201 (58.5%) children contractingHIV The median age of children was 20 months. Therewere 121 (35.4%) cases involved in prevention of motherto-child transmission. Triple-drug antiretroviral therapywas prescribed to 78.1 o/o children. The most frequentmorbidities were chronic diarrhea, wasting syndrome, andoropharyngeal candidiasis. Thirty-six children died; mostlydue to sepsis (30.5%)Conclusion The majority of cases of HIV were between 1and 5 years old. The most frequent morbidities were chronicdiarrhea, wasting syndrome, and oropharyngeal candidiasis.Thirty-six children died mostly due to sepsis. The preven-tion program for mother-to-child transmission should beencouraged among pregnant women who are known to beHIV-positive.